SCHOOL SMART SERVICE: SEBAGAI LAYANAN PENERIMAAN PESERTA DIDIK BARU SISTEM INFORMASI BERBASIS WEBSITE - Yunitasari, Yunitasari; Muslihudin, Muhamad (JECE (Journal of Ethics and Character Education), 2024)
The development of today's information technology has become increasingly sophisticated and penetrated into various fields, one of which is education. In the world of education that really needs information, the website is expected to fulfill that information need. This high school has quite a lot of enthusiasts so that the management of new student data is a little more difficult and tends to be slow because the management is still manual. With this information system, later the registration process and data management will be able to run practically and efficiently. The purpose of this research is to design and build an online information system for new student admissions. Use case diagrams, squance diagrams and other tools ERD entity relationship diagrams. The next stage is implementing the system. The method used in system design is the waterfall method. In the design of this information system helps in making the information system by looking at the stages in the model starting from the requirements stage suitable for the development of the system that was first designed. The use of the waterfall method is able to provide convenience in managing website-based new student admissions and minimize errors that might occur in the system. After the system is created, prospective students who want to register will find it easier and do not have to meet face to face during registration.